Profiling Cancer Gene Mutations in Clinical Formalin‐Fixed, Paraffin‐Embedded Colorectal Tumor Specimens Using Targeted Next‐Generation Sequencing. (24th March 2014) - Zhang, Liangxuan; Chen, Liangjing; Sah, Sachin; Latham, Gary J.; Patel, Rajesh; Song, Qinghua; Koeppen, Hartmut; Tam, Rachel; Schleifman, Erica; Mashhedi, Haider; Chalasani, Sreedevi; Fu, Ling; et al.
Abstract : Purpose: The success of precision oncology relies on accurate and sensitive molecular profiling. The Ion AmpliSeq Cancer Panel, a targeted enrichment method for next‐generation sequencing (NGS) using the Ion Torrent platform, provides a fast, easy, and cost‐effective sequencing workflow for detecting genomic "hotspot" regions that are frequently mutated in human cancer genes. Most recently, the U.K. has launched the AmpliSeq sequencing test in its National Health Service. This study aimed to evaluate the clinical application of the AmpliSeq methodology. Methods: We used 10 ng of genomic DNA from formalin‐fixed, paraffin‐embedded human colorectal cancer (CRC) tumor specimens to sequence 46 cancer genes using the AmpliSeq platform. In a validation study, we developed an orthogonal NGS‐based resequencing approach (SimpliSeq) to assess the AmpliSeq variant calls. Results: Validated mutational analyses revealed that AmpliSeq was effective in profiling gene mutations, and that the method correctly pinpointed "true‐positive" gene mutations with variant frequency >5% and demonstrated high‐level molecular heterogeneity in CRC. However, AmpliSeq enrichment and NGS also produced several recurrent "false‐positive" calls in clinically druggable oncogenes such as PIK3CA . Conclusion: AmpliSeq provided highly sensitive and quantitative mutation detection for most of the genes on its cancer panel using limited DNA quantities from formalin‐fixed, paraffin‐embedded samples. For those genes with recurrent "false‐positive" variant calls, caution should be used in data interpretation, and orthogonal verification of mutations is recommended for clinical decision making. Abstract : The authors used 10 ng of genomic DNA from formalin‐fixed, paraffin‐embedded human colorectal cancer tumors to sequence 46 cancer genes using the AmpliSeq platform. They developed an orthogonal resequencing approach, SimpliSeq, to evaluate the clinical application of AmpliSeq. The results suggest that AmpliSeq provides highly sensitive and quantitative mutation detection for most genes on its cancer panel; however, verification testing is critical for low‐abundance variants and genes that are found to have recurrent false‐positive variants. Abstract : 摘要 目的 精确肿瘤学的成功依赖于准确和灵敏的分子分析。Ion AmpliSeq 癌症分析板是利用离子激流测序（Ion Torrent）平台的新一代测序（NGS）靶向富集法，可提供快速、简便且具成本效益的测序流程，用以检测人类癌症基因中频繁突变的基因组"热点"区域。最近，英国在其国家医疗服务体系中推行了 AmpliSeq 测序检测。这项研究旨在评估 AmpliSeq 方法的临床应用。 方法 我们从由福尔马林固定、石蜡包埋的人结直肠癌（CRC）肿瘤样本中提取了 10 ng 基因组 DNA ，利用 AmpliSeq 平台对 46 个癌症基因进行测序。在一项验证研究中，我们开发了一种以 NGS 为基础的正交重新测序法（SimpliSeq），以评估 AmpliSeq 变体识别。 结果 验证的突变分析显示，AmpliSeq 可有效剖析基因突变，该方法正确地确定了变异频率 >5% 的"真阳性"基因突变，证实了 CRC 的高水平分子异质性。然而，在临床上可予用药的致癌基因（例如 PIK3CA ）中，AmpliSeq 富集法和 NGS 也会产生一些复发的"假阳性"识别。 结论 利用从福尔马林固定、石蜡包埋样本中提取的有限 DNA 数量，AmpliSeq 对其癌症分析板中的大部分基因提供了高度灵敏的定量突变检测。对于那些出现复发的"假阳性"变体识别的基因，在进行数据解读时应谨慎，建议在临床决策时进行正交突变验证。 The Oncologist 2014;19:336–343